2021
DOI: 10.1002/ccd.29894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a suspended radiation protection system to reduce operator exposure in cardiology interventional procedures

Abstract: Objectives To investigate a novel suspended radiation shield (ZG), in reducing operator radiation exposure during cardiology interventions. Background Radiation exposure to the operator remains an occupational health hazard in the cardiac catheterization laboratory. Methods An anthropomorphic mannequin simulating an operator was placed near a phantom, simulating a patient. To measure the operator dose reduction, thermoluminescent detectors (TLDs) were inserted into the head and into the eye bulbs of the manneq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
9
2
Order By: Relevance
“…The measurements exhibited high attenuation of doses in the areas, where dosimeters were shielded by the ZG system; in particular, in the region of chest and the eye lens where at least 15-fold and threefold reduction of doses, respectively, is predicted. The effectiveness of the ZG system in reducing the exposure to the eye lens found in this study is lower than that reported by Savage et al ( 2013 ) (66% vs. 87% reduction for eye &head region) and Zanca et al ( 2021 ) (66% vs. 79%/83% reduction for the left eye in CA/PCI procedures) while higher than that reported by Haussen et al ( 2016 ) (66% vs. 50%). In quoted studies, except for the Zanca et al ( 2021 ), the operators performed different non-cardiac interventional radiology procedures.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The measurements exhibited high attenuation of doses in the areas, where dosimeters were shielded by the ZG system; in particular, in the region of chest and the eye lens where at least 15-fold and threefold reduction of doses, respectively, is predicted. The effectiveness of the ZG system in reducing the exposure to the eye lens found in this study is lower than that reported by Savage et al ( 2013 ) (66% vs. 87% reduction for eye &head region) and Zanca et al ( 2021 ) (66% vs. 79%/83% reduction for the left eye in CA/PCI procedures) while higher than that reported by Haussen et al ( 2016 ) (66% vs. 50%). In quoted studies, except for the Zanca et al ( 2021 ), the operators performed different non-cardiac interventional radiology procedures.…”
Section: Discussioncontrasting
confidence: 83%
“…The effectiveness of the ZG system in reducing the exposure to the eye lens found in this study is lower than that reported by Savage et al ( 2013 ) (66% vs. 87% reduction for eye &head region) and Zanca et al ( 2021 ) (66% vs. 79%/83% reduction for the left eye in CA/PCI procedures) while higher than that reported by Haussen et al ( 2016 ) (66% vs. 50%). In quoted studies, except for the Zanca et al ( 2021 ), the operators performed different non-cardiac interventional radiology procedures. The difference suggests that the performance of the ZG system might depend on dynamic factors related to clinical practice, such as the projection types used, the physician’s position with respect to the center of X-ray field, exposure parameters depending on patient size and the treatment area etc.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Cardiac catheterization procedures account for about 40% of total medical radiation exposure [2,21]. Despite the progress in X-ray instrumentation, protection devices, the introduction of robotic PCI, and foremost the increased awareness, the progressively increasing complexity of the procedures performed (including structural and valvular procedures) leads to a constant increase in operator exposure [22][23][24]. This increase was recently quantified in a 54% higher average fluoroscopy time when procedures performed in the year 2016 were compared to those performed 10 years before [25].…”
Section: Radiation Exposure In Interventional Cardiology and Interpretation Of The Present Findingsmentioning
confidence: 99%
“…The body of the suit is composed of materials having a thicker lead equivalency than conventional lead aprons and has a transparent acrylic shield extending upward to protect the operator's head and neck. Although these design elements may theoretically offer superior radiation protection compared to lead aprons, studies evaluating the suspended lead suit have been limited to ex vivo investigations, 6–8 to small studies in noncardiac fluoroscopically guided procedures, 9–11 to its use exclusively during the percutaneous coronary intervention (PCI), 12 or did not account for important procedural variables known to impact physician radiation doses when evaluating the impact of suspended lead 13 . Furthermore, none of the prior studies investigated whether the suspended lead suit, when worn by the primary operator, impacted the radiation doses of other members of the catheterization laboratory team.…”
Section: Introductionmentioning
confidence: 99%